2020
DOI: 10.4136/ambi-agua.2451
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate riparian zone use directly decreases water quality of a low-order urban stream in southern Brazil

Abstract: Considering the current importance watercourses quality conservation, it is important to establish relationships between parameters that enable evaluation of the origins of changes in water quality, allowing actions to mitigate them. However, it is important to improve the association of different variables and to take sufficient samples. This study associates usual techniques and parameters to analyse the water quality of an urban river from Paraná State, Brazil. For this, we used biological indicators (aquat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Zequi et al, 2019). The lowest values found here are similar to the highest value found near headwater in an urban watercourse from the same municipality (Crisigiovanni et al, 2020). The %Chironomidae was very lower than found in agriculture-associated sites (Zequi et al, 2019), but similar to that found in protected sites (e.g.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Zequi et al, 2019). The lowest values found here are similar to the highest value found near headwater in an urban watercourse from the same municipality (Crisigiovanni et al, 2020). The %Chironomidae was very lower than found in agriculture-associated sites (Zequi et al, 2019), but similar to that found in protected sites (e.g.…”
Section: Resultssupporting
confidence: 75%
“…In this way, the relationship between land use and occupation and the water quality values found by the evaluation of macroinvertebrates showed reasonable values for biotic indices and RAPHD, mainly compared to the quality of rivers in the region, both in urban and rural areas (e.g. Crisigiovanni et al, 2020).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Fractional vegetation cover (FVC): Vegetation plays a crucial role in slowing surface runoff and enhancing water conservation capacity [56,57]. Considering the positive influence of vegetation on UBS, FVC is an essential indicator in this study.…”
Section: Data and Resourcesmentioning
confidence: 99%